The Impact of Reference Guidance Services on UNS Student’s Reading Interest in Biographical Collection - Ilmi, Bachrul; Itsnaini, Afifah; Imourani, Cheisya Kinanti; Revadhilasari, Yeaz Salwa (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
The biography collection is one part of the reference collection needed by the library users. In a library there is a guidance service that helps its users fulfill their information needs. The purpose of this research is to find out why reference guidance services can affect the level of student reading interest in the biography collections. The writing of this article, using the explanatory method with a quantitative approach in the form of data collection through questionnaires distributed to active students at Sebelas Maret University. The results show that the quality of reference guidance services provided in a library can affect reading interest in biography collections, such as the friendliness and attentiveness of reference librarians in serving and providing guidance to users. A good guidance service can increase library users' reading interest in a biography collection.